1987
DOI: 10.3354/meps036081
|View full text |Cite
|
Sign up to set email alerts
|

Deep water vegetations of Lobophora variegata (Phaeophycae) in the coral reef of Curagao: population dynamics in relation to mass mortality of the sea urchin Diadema antillarum

Abstract: Cover, blade size, growth rate, longevity and reproduction of the foliose brown macroalga Lobophora variegata (Lamouroux) Womersley were recorded in 2 deep-water populations (25 to 35 m) in the coral reef of Curaqao (Netherlands Anhlles) for over a year. No seasonal effects were observed. Although mean cover was relatively constant, turnover rates were very high with half-life of blades being, on average, only ca 20d. During t h s study the herbivorous sea urchin Diadema a n t i l l a m Philippi suffered mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 19 publications
0
47
0
Order By: Relevance
“…This variation may be a consequence of its morphological plasticity as a direct response to grazing (de Ruyter van Steveninck & Breeman 1987a, b, 1988a. Such changes have been observed for Padina jamaicensis which undergoes a morphological shift from a prostrate turf morphology to an erect foliose form in response to herbivore moderation (Lewis et al 1987 forms retain their form when transplanted to other habitats or when herbivorous fishes are excluded with cages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This variation may be a consequence of its morphological plasticity as a direct response to grazing (de Ruyter van Steveninck & Breeman 1987a, b, 1988a. Such changes have been observed for Padina jamaicensis which undergoes a morphological shift from a prostrate turf morphology to an erect foliose form in response to herbivore moderation (Lewis et al 1987 forms retain their form when transplanted to other habitats or when herbivorous fishes are excluded with cages.…”
Section: Discussionmentioning
confidence: 99%
“…Populations with resistant attributes are generally distributed in habitats with moderate to high fish herbivore abundance, whereas susceptible populations (ruffled form) are restricted to habitats with low fish abundances or in spatial refuges in areas of high fish grazing. Thus, it seems likely that herbivores play an important role, along with other environmental factors, in maintaining these 3 forms and their distributions in Belize and elsewhere (Morrison 1986, 1988, de Ruyter van Steveninck & Breeman 1987a, b 1988a.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lobophora variegata is a widespread and common alga on Caribbean reefs (van der Hoek et al 1978, Hughes 1994, Ruyter van Steveninck & Breeman 1987, Diaz-Pulido & Diaz 1997 and worldwide (Jompa & McCook 2002a,b). It is often found overgrowing live tissue of scleractinian corals (Ruyter van Steveninck et al 1988) and has been shown to cause coral mortality in the Indo-Pacific branching coral Porites cylindrica (Jompa & McCook 2002a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Mass mortality was caused by a virulent biotic disease (Bak et al 1984, Hughes et al 1985. Elimination of D. antillarum from most Caribbean reefs resulted in a significant increase of fleshy and filamentous algae as well as of some macroalgae (Hughes et al 1985, de Ruyter van Steveninck & Bak 1986, de Ruyter van Steveninck & Breeman 1987. This increase was achieved at the expense of other benthic organisms such as corals, crustose corallines and clionid sponges whose settlement has been considerably reduced (de Ruyter van Steveninck & Bak 1986, Liddell & Ohlhorst 1986.…”
Section: Widespread Disease-related Mass Mortalities Ofmentioning
confidence: 99%